The Result Of CCG 1961 Protocol Treatment With High Risk Acute Lymphoblastic Leukemia In Children - Huong, Nguyen Thi Mai; Vien, Bui Van; Ha, Tran Thu; Lan, Bui Ngoc; Lan, Phung Tuyet; Huong, Nguyen Thi (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Acute lymphoblastic leukemia (ALL) remains the most common malignancy in children. It accounts approximately 75% of all cases of childhood leukemia. High risk ALL in children can be cured treatment of high risk ALL in children at National Children’s Hospital (NCH). Methods: Prospective study 102 patients from 6/2008 to 12/2012. The patients of high risk ALL was with the SPSS program. Results: 88.24% achieved initial complete remission. According to Kaplan Meyer 5 years: 5- year overall survival (OS) is 48.6% ± 5.0; 5- year event free survival (EFS): 46% ± 5.0. Treatment of boys was better than of girls: OS and EFS were 54.8% and 52.9% compare with 30.5% and 29.6% respectively (p< 0,05). Rapid early response (RER) group had OS and EFS higher than slow early response (SER): 49.6% and 47.8% vs. 31.5% and 30.4%. Conclusion: Overall survival and event free survival was 48.6% and 46%. Relapse rate was 16.7%. Mortality rate was 37.25%.